Effect of MgO Content on Melting Features and Viscosity of SiO2-CaO-MgO-Al2O3-FeO Slag in Nickel Laterite Metallurgy - Pan, Cheng; Lv, Xuewei; Bai, Chenguang; Liu, Xuyang; Li, Donghai (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
Physic-chemical properties of slag at high temperature play an important role in the pyro-metallurgical process of production of ferronickel alloy. It determines the operation efficiency, metal recovery ratio, energy consumption and the distribution of elements like S and P between the slag and metal. In the present work, the effect of MgO content in the slag on melting features and viscosity of the slag was investigated. The MgO content in the SiO2-CaO-MgO-Al2O3-FeO quinary slag system varied from 16% to 22.5%. The results shown that all slag samples begin to softening at the same temperature, and the softening temperature, melting temperature, flowing temperature decrease with the increase of MgO content when the MgO content is in range of 16 and 20.5 pct mass, and when MgO content up to 22.5 percent, the temperatures increase sharply. Besides, the inflection point temperature of viscosity-temperature curve increase with the increase of MgO when the MgO content is in range 16 and 22.5 pct mass.